ANALISIS USAHATANI SINGKONG DI KAMPUNG ADAT CIREUNDEU KELURAHAN LEUWIGAJAH, KECAMATAN CIMAHI SELATAN - Haryono, Audie Amanda; Suminartika, Eti (Agros Journal of Agriculture Science, 2024)
In Cireundeu Traditional Village, cassava is a staple food, but its production has been declining every year. However, the unique characteristics of cassava as a staple food and the Sundanese culture in Cireundeu Customary Village make it an attractive destination for tourists, whose numbers increase annually. This has led to to increase cassava production. This research analyzes the income and contribution of cassava farming. The research method used a quantitative descriptive approach. Data were analyzed using mathematical analysis. The results show that farmers produce an average of 5.312,5 kg/ha/year of cassava, with cash income amounting to IDR 7.604.816,78/ha/year and a R/C ratio of 4,88. Based on net income calculations, cassava farming shows a negative value (incurs losses) of IDR 15.143.855,22/ha/year. However, from a social perspective, cassava farming is closely related to the preservation of Sundanese culture and beliefs, as well as serving as a recreational site (Ekoeduwisata Cireundeu Traditional Village).